Competences of nurses in hospital services for effective health management in the context of a pandemic (Research, Society and Development, 2021)
Introduction: Given the various attributions assigned to nurses, the intensification in the work process arose from the pandemic context. It is essential to improve skills, aiming to collaborate for assistance and quality management. Objective: Recognize the Competencies of Nurses for Effective Health Management in hospital services in a pandemic context. Methods: Study approved by FAMERP Research Ethics Committee, Opinion nº 4027756, of 05/14/2020. Cross-sectional study with descriptive design, quantitative analytical approach. Online questionnaire applied, consisting of characterization, assessment, and ranking of the importance of the competencies and self-assessment. We included nurses working in the hospital in the following three main areas: care, clinical, and managerial for more than three months, and we excluded resident nurses and those on vacation, maternity leave, or medical leave. Results: According to the Competencies Assessment, some that stood out negatively were: Performing bureaucratic activities, Ethics, and morals, know how to listen to the patients, Patience, Following the Institution's Rules, Correct record in the medical record, Reporting all complications, Nursing Care Systematization, Research development, Technological knowledge and Training, and professional development. Conclusion: The study contributes to an expanded view on the importance of skills in the work process of nurses for effective health management.